A Study of Levels and Characteristics of innovation activity (Global Journal of Management and Business Research, 2012)
The importance of innovation in organizations#xB4; competitiveness is an undeniable fact. Innovations reflect a critical way in which organizations respond to either technological or market challenges. Small and Medium sized enterprises (SMEs) constitute 94 % of Iranian firms. According to Iran statistic website the value added of 94 % of Iranian firms is just about 10 % of the whole value added in country. This study assumes the lag of innovation is the reason of uncompetitive nature of Sistan Baluchestan SMEs. This paper reports on the results of a study that examined barriers to firms’ innovation among a sample of 86 managers of small and medium-sized enterprises (SMEs) in Sistan Baluchestan. Findings of the study show that the most significant barriers are associated with costs, whereas the least significant are associated with lag of information. The survey results show that Sistan Baluchestan SMSs are not collaborating with universities and higher education institutions; they do not see university as a main source of information. Then it is not a surprising point that 29.0 % unemployment rate is reported in 2009 however 50 % of studied SMEs reported lack of skilled labour as a barrier to innovation.
Keywords: innovation; Barriers to innovation and SMEs; Sistan